Túa Blesa, poetic ardor - Saldaña, Alfredo (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The original and relevant contribution of Túa Blesa to literary studies in our country is analyzed in these pages, a contribution that has made him an exceptional hermeneutic, that is, the exception of literary hermeneutics.